PENGELASAN DISIMILAR MATERIAL (DUPLEX STAINLESS STEEL) 2205 DAN (HIGH STRENGTH STEEL) GRADE VL D36 UNTUK KAPAL OIL TANKER - Maycal Yudistira; Julius (Fakultas Sains dan Teknologi Universitas Karimun, 2021)
The choice of Duplex Stainless Steel material for oil tanker ship construction is very appropriate because in addition to having good mechanical properties (high tensile and yield strength and toughness) as a ship construction structure, it is also resistant to loads of highly corrosive liquid chemicals. Unlike Mild Steel or Duplex Stainless Steel A, welding and treating Duplex Stainless Steel requires very strict procedures and care must be taken. The choice of welding process, namely a combination of (Flux Cored Arc Welding) and SAW (Submerged Arc Welding) is a welding process that is very suitable for welding ship construction. The welding process is categorized as a semi-automatic and automatic welding process that can increase productivity while speeding up welding work. This paper illustrates the welding of two materials with different specifications, namely Duplex Stainless Steel 2205 plate material and VL D36 plate material, along with practical instructions for welding it up to the things that must be considered regarding the handling procedure. In welding Duplex Stainless Steel 2205 plate material it is very important to keep the heat input in the range of 0.5-2.5 kj / mm.